Pengaruh Work Overload terhadap Stres Kerja di PT. Citra Nusantara Catering yang Berdampak pada Kepuasan Customer - Siti Nuroh; Puji Isyanto; Dini Yani (J-MAS (Jurnal Manajemen dan Sains), 2023)
Due to their role in the implementation of company policies and operational activities, human resources are an important asset in a business organization. Companies' resources, such as capital, methods, and machines, cannot produce optimal results without the support of optimally performing human resources. In order to achieve objectives and carry out the company's functions and objectives, employees play a crucial role in any organization. Employees develop into planners, executors, and controllers who constantly actively contribute to the achievement of an organization's, industry's, or business's goals.The achievement of goals is supported by employees, but employees' attitudes toward work are also influenced by their own thoughts, feelings, and desires. These attitudes are referred to as work-related satisfaction, stress, and frustration, as well as work overload, environment, needs, and so forth. Employees' unhealthy thoughts will result in customer dissatisfaction due to high stress and low motivation.Workplace stress is typically viewed as a negative condition. However, because stress arises as a result of pressure from superiors and the work environment, including customer satisfaction, at a certain level, work stress can improve employee performance. For instance, if a worker has a specific goal that requires more effort than usual, he or she will experience stress.Companies must be careful to identify shifts in consumer needs and desires, which change almost constantly, in order to satisfy customers. Buyers will move after forming perceptions of the offer's value, the performance of the company's employees in service, and customer satisfaction following purchase, depending on how the company presents its offer. The level of one's feelings after comparing (performance or results) to his expectations is known as consumer satisfaction.